Stratigraphy, structural setting and burial history of the Messinian Laga basin in the context of Apennine foreland basin system - Bigi, Sabina; Milli, Salvatore; Corrado, Sveva; Casero, Piero; Aldega, Luca; Botti, Flavia; Moscatelli, Massimiliano; Stanzione, Olivier; Falcini, Federico; Marini, Mattia; Cannata, Domenico (Journal of Mediterranean Earth Sciences, 2014)
An integrated approach to the study of the Central Apennines thrust system has been conducted, combining together new field, geophysical, organic matter maturity and mineralogical datasets. The area comprises one of the most studied basins of the Central Apennines: the Laga basin. It developed during the Messinian time and represents the link between the internal, uplifted, Lower Miocene fold-and-thrust belt to the west, and the external, more recent part of the chain, buried below a thick pile of synorogenic, Plio-Pleistocene clastic deposits of the Periadriatic basin to the east. The Laga basin is filled by several turbiditic sedimentary sequences, largely studied in the past and mostly included into the Laga Formation, classically considered the fill of a deep marine foredeep basin connected to the flexure of the subducted Adriatic lithosphere under the Apennines. Our results clearly suggest that during Messinian, the main factor controlling depositional system architectures was thrusts activity, which governed the localization of the main depocenter in the basin and its eastward space-time migration. The occurrence of thrust activity during deposition of most of the Laga basin sedimentary succession suggests that it can be described as an internally deformed but not migrating sedimentary wedge, having features recording the transition from foredeep to wedge top depozone.